Estrogen-Induced Extracellular Calcium Influx Promotes Endometrial Cancer Progress by Regulating Lysosomal Activity and Mitochondrial ROS - Shen, Boqiang; Hao, Juan; Lin, Yanying; Li, Xingchen; Yang, Xiao; Huang, Ting; Wang, Jiaqi; Jia, Yuanyuan; Zhou, Jingyi; Wang, Jianliu (Frontiers in Medicine, 2022)
Objective Calcium is present in serum mainly in filterable and bound forms, and Ca2+ is a central key to modulate signaling pathways that control oncogenesis and oncochannels associated with several types of cancer. However, the biological significance of serum calcium, as well as its related mechanism with estrogen in endometrial cancer (EC) still remains elusive. This study aims to ascertain the relationship between serum calcium and clinicopathology in EC. Methods Retrospective assessment of a total of 502 patients diagnosed with EC after surgery in Peking University People's Hospital from 2010 to 2018. Preoperative serum ionized calcium and the albumin corrected calcium was calculated in quartiles for various postoperative clinicopathological characteristics, logistic regression adjusted for potential confounders. Intracellular calcium homeostasis change induced by estrogen was detected by confocal analysis. Downstream pathways were analyzed by transcriptome and proteomics. Mitochondrial Ca2+ and ROS level was detected by confocal and flow cytometry. Lysosomal morphological and membrane changes were all verified by confocal or Western blot assays. Results A high level of albumin-corrected serum calcium was significantly correlated with EC clinicopathological characteristics progression include lymph vascular space invasion, lymph nodes metastasis, myometrial invasion, and cervical invasion. Calcium homeostasis is regulated by estrogen in EC cells derived from extracellular calcium influx but not the release of the endoplasmic reticulum. Proteomic and bioinformatic analysis revealed the calcium influx may be involved in the regulation of autophagy and mitochondrial-related pathways. The mechanistic investigation demonstrated that calcium influx acted on the function of mitochondrial ROS and lysosomal activity. Conclusion Our findings revealed serum calcium level was significantly related to poor outcomes and the extracellular calcium influx induced by estrogen should be targeted to original preventive strategies in EC.